Analysis of the Container Dwell Time at Container Terminal by Using Simulation Modelling - Radifan Hassan; Raja Oloan Saut Gurning (International Journal of Marine Engineering Innovation and Research, 2020)
One of the parameters that affecting efficiency of container terminal is dwell time (DT). The more least the DT the more efficient a container terminal would be. As the government regulations of the Ministry of Transportation that stated in Number PM 25 in 2017 in Article 2 Paragraph 1 explains that the maximum dwell time must not exceed than 3 days. The purpose of this study is to identify the major factor of prolonged DT in a container terminal. The authors used discrete event simulation to model the system inside the container terminal operation by using Arena Simulation software. The Root Cause Analysis (RCA) is being used for the data analysis and finding the root cause. The container handling inside the container terminal data is collected, then the effect container of handling the equipment on dwelling time was testified by creating a model then analyzed. The result of the simulation is that there is a small impact from container handling equipment towards DT. From the Problem Tree framework that created based on the operational data and interviews. It shows that the most DT is contributed by the prolonged time of container stay at container yard.